Cardiac parameters and endothelial function in a strength athlete: a case report - Guilherme B. Grezzana; David W. Moraes; Diego V. Silva; Bruna Eibel; Maximiliano I. Schaun; Alexandre M. Lehnen (Universidade Estadual Paulista (UNESP), 2018)
Abstract Aims: We aimed to discuss a case of strength training athlete who competes in international competitions regarding cardiac (dimension and function), vascular (endothelium and vascular resistance), hemodynamic (blood pressure), given limited evidence supporting these cardiovascular adaptations as well as concerning endothelial function in long-term high-intensity strength training. Methods: We assessed heart structure and function (echocardiography); systolic (SBP) and diastolic blood pressure (DBP); endothelium-dependent vasodilation (flow-mediated dilation, FMD); maximum force tested in the squat, bench press, and deadlift; and maximum oxygen consumption (spirometry). Results: powerlifter's cardiac dimensions (interventricular septum 13 mm; posterior wall thickness 12 mm; LV diastolic diameter 57 mm; left ventricle mass 383 g; LV mass adjusted by body surface area 151.4 g/m2) are above the proposed cutoff values beyond which pathology may be considered. Moreover, cardiovascular function systolic (ejection fraction by Simpson's rule, 71%) is preserved and FMD measure is fairly close and above normal; however, a mild increase in systolic and diastolic blood pressure was observed (130/89 mmHg, respectively). Conclusion: Cardiac remodeling cannot be viewed as either pathological or harmful to the cardiovascular system. Furthermore, we showed an improvement in endothelial function.